Research on the potential for academicians to work from home: Research in a Malaysian public university - Osman, Wan Nadzri; Radzuan, Kamaruddin; Zulhumadi, Faisal; Mohd Nawi, Mohd Nasrun (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2020)
The year 2020 has witnessed the world being swept by the Covid-19 pandemic that has greatly changed the social and economic landscapes of many countries globally. Among the changes brought upon by this pandemic involves the way one works. With the spread of this pandemic, residents in many areas have begun to benefit from the use of various technologies in many activities, including sales and purchase, and performing work in order to minimise from being exposed to activities outside the house. This research was performed with the aim to look at the potential of implementing a work from home programme among the academic staff in a public university in Malaysia. A questionnaire was distributed to observe the feedback regarding the implementation of this programme, and it was revealed that almost all academic staff believed that this programme can be established for academic staff and they stated their readiness to be involved and support the implementation of such a programme.